Prototype of a Floating-Type Nanohydro Generator as a Lighting Energy Source for Agricultural Land - Pauzi, Gurum Ahmad; Putra, Dio Aditia; Supriyanto, Amir; Suciyati, Sri Wahyu (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
A floating-type nano-hydro generator prototype has been developed as a source of electrical energy for lighting in agricultural areas. This generator is designed to produce electrical energy without modifying the flow medium, making it easy to apply in various water channels such as irrigation systems, small rivers, and large rivers, as the generator can automatically adjust to the ebb and flow of water. The electricity generated benefits agricultural lands far from PLN (Indonesia's state electricity company) power sources. The average voltage produced in this study was 19.19 volts, with an average generator speed of 30.1 rpm and a turbine speed of 104.4 rpm. Meanwhile, testing results showed voltages ranging from the lowest rotation of 8 volts to the highest rotation of 56 volts. The voltage output from this device can be used to power lights or other small electrical needs.